2015
DOI: 10.18203/2320-6012.ijrms20150152
|View full text |Cite
|
Sign up to set email alerts
|

A study on the incidence of retromolar foramen in South Indian adult dried human mandibles and its clinical relevance

Abstract: INTRODUCTIONThe retromolar foramen is an accessory foramen of the mandible situated in the retromolar fossa. The triangular depression between the temporal crest and the anterior border of the ramus of mandible is called the retromolar fossa. Nerves may pass from the substance of temporalis to enter the mandible through the retromolar fossa, where they communicate with branches of the inferior alveolar nerve. Foramina occur in 10% of retromolar fossa and infiltration in this region can abolish sensation which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…However, it can be located as close as 1 mm from the tooth [29]. It lies 8.02 mm from the anterior aspect of the branch [4,31]. It is closer to the buccal cortex than to the lingual plate [4].…”
Section: Morphometric Measurement Of Rmfmentioning
confidence: 99%
“…However, it can be located as close as 1 mm from the tooth [29]. It lies 8.02 mm from the anterior aspect of the branch [4,31]. It is closer to the buccal cortex than to the lingual plate [4].…”
Section: Morphometric Measurement Of Rmfmentioning
confidence: 99%
“…However, it can be located just 1 mm away from the tooth (Shantharam et al, 2013). It is 8.02 mm from the anterior border of the ramus (Motamedi et al, 2016; Tiwari et al, 2015). Motamedi et al (2016) reported that it is located closer to the buccal cortex than the lingual plate.…”
Section: Retromolar Foramenmentioning
confidence: 99%
“…Various Indian studies reported varying incidences of RMF in the different ethnic groups, nuances are still lacking [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A prominent issue is the nomenclature and categorization of RMF/RMC as reported in various literatures. Some authors considers that RMF/RMC as the bifid or trifid collateral of the main conduit, the mandibular canal, initiating at the mandibular canal and terminating at the retromolar trigone (RMT) [6][7][8][9][10][11][12][13][14][15][16][17][18]. While, Other researchers imply that RMC is as an unique separate entity, emphasizing its clinical relevance [19,20].…”
Section: Introductionmentioning
confidence: 99%